ORALLY DISINTEGRATING PREPARATIONS: RECENT ADVANCEMENT IN FORMULATION AND TECHNOLOGY - Thakur, Reeta Rani; Rathore, Devnder Singh; Narwal, Sonia (Journal of Drug Delivery and Therapeutics, 2012)
Oral route is the most convenient route for drug administration due to the highest component of compliance mainly the pediatrics and geriatrics. It is regarded as the most economical and safest method of drug delivery. Formulation of a orally disintegrating dosage form is beneficial for patients suffering from motion sickness, repeated emesis, mental disorder and dysphasia because they cannot swallow large quantity of water and it is easy to administer. The unique property of orally disintegrating dosage form is that they are readily disintegrating and dissolves in saliva and avoids the requirement of water which is the major benefit over conventional dosage form. Further, drug having the satisfactory absorption from the oral mucosa can be formulated in such type of dosage form. Since the drug is completely released in the mouth, so taste masking of active ingredient becomes essential for formulating orally disintegrating dosage form. This article includes requirement for orally disintegrating tablets, orally disintegrating films, chewing gums, oral wafers and buccal patches ,their advantages,disadvantages,challenges in formulation ,patented technologies, various technologies developed for formulated orally disintegrating dosage form ,super disintegrating agents in the formulation, evaluation method and various marketed products.